Implementation Of Perfomance Management in The Deming Model at Satpol PP Office - Bayu Apriadi Tanjung; Diva Buanaria; Liffia Simanjuntak; Muhammad Izaz Miarzo; Satriadi (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2024)
This study aims to describe the implementation of the Deming Model performance management (PDCA cycle) at the Tanjungpinang City Satpol PP office. The type of research used is descriptive research with a qualitative approach, with data obtained through in-depth interviews with Mr. Ray as secretary, and staff involved in daily operations, as well as direct observation. Data analysis uses thematic analysis techniques that include three main steps: data reduction, data presentation, and conclusion drawing. The results showed that the implementation of the PDCA cycle at the Tanjungpinang City Satpol PP office has had a positive impact on improving organizational performance. Through structured stages from planning (Plan), implementation (Do), checking (Check), to corrective action (Act), the Satpol PP Office is able to plan and implement policing programs more effectively and efficiently. However, there are obstacles such as lack of training, budget limitations, and suboptimal coordination between sections. Performance evaluation needs to be improved in terms of more integrated measurement and monitoring. The implications of this study emphasize the importance of coordination and systematic evaluation for continuous improvement.